Social Websites: A Blessing or Curse? Through the Lense of University Students - Kalim Ullah; Rohi Gul; Wajeeha Mukhtar; Rabia; Muhammad Mustafa; Naeem Ullah (Dialogue Social Science Review (DSSR), 2025)
The present study mainly aimed at knowing about “Perceptions of Social Websites Among University Students.” It was a descriptive type of research. The researcher had the objectives including identifying the perceptions of students regarding social websites. Also, the purpose of their usage on the part of students. A questionnaire with 20 items was used for data collection and students of social sciences department at Abdul Wali Khan university Mardan was the population of the study. A random sample of 100 students was selected. The findings show that maximum number of students were of the view that social websites are used for learning purposes. However, it was further revealed that these social websites are also used for communication and interaction with the near and dear ones. Some of the respondents also opined that these websites are used as hobby and entertainment as well.